2016
DOI: 10.4097/kjae.2016.69.4.362
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative interscalene brachial plexus block aids in perioperative temperature management during arthroscopic shoulder surgery

Abstract: BackgroundHypothermia is common during arthroscopic shoulder surgery under general anesthesia, and anesthetic-impaired thermoregulation is thought to be the major cause of hypothermia. This prospective, randomized, double-blind study was designed to compare perioperative temperature during arthroscopic shoulder surgery with interscalene brachial plexus block (IBPB) followed by general anesthesia vs. general anesthesia alone.MethodsPatients scheduled for arthroscopic shoulder surgery were randomly allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…The temperature of our patients could have been higher than that in the study of Lim et al [20] due to prewarming and intraoperative warming in our study.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The temperature of our patients could have been higher than that in the study of Lim et al [20] due to prewarming and intraoperative warming in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…Lim et al [20] have shown that ISBPB procedure can reduce the risk of perioperative hypothermia caused by anestheticimpaired thermoregulation by decreasing the requirement of general anesthetics. The temperature of our patients could have been higher than that in the study of Lim et al [20] due to prewarming and intraoperative warming in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al [ 8 ] reported that performing ISBPB in the preoperative period with general anesthesia reduced the amount of inhalation anesthetic required and consequently decreased the degree of perioperative hypothermia. A combination of general anesthesia and ISBPB may be beneficial for perioperative temperature management by reducing the impairment of thermoregulation by anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been reported to prevent hypothermia during an arthroscopic shoulder surgery [ 1 , 2 , 8 13 ], and only few studies assessing interscalene brachial plexus block (ISBPB), which is widely used for postoperative pain control in shoulder surgery, have been reported [ 8 10 ]. A previous study reported that preoperative ISBPB can be useful in preventing hypothermia by reducing the amount of volatile anesthetics in patients undergoing arthroscopic shoulder surgery under general anesthesia [ 8 ]. However, other studies have reported that hypothermia occurs more frequently in elderly patients or when active warming is not performed despite using preoperative ISBPB with general anesthesia [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of thermoregulatory defense mechanisms during general anesthesia is dose-dependent and mostly results in perioperative hypothermia [ 6 ]. In this issue of Korean Journal of Anesthesiology ( KJA ), Lim et al [ 7 ] report that a combined interscalene block and general anesthesia reduced the concentration of desflurane and prevented intraoperative hypothermia during arthroscopic shoulder surgery. The core temperature of patients who receive only an interscalene block should be monitored to evaluate the effect of the block alone.…”
mentioning
confidence: 99%